Analisis Tegangan Tulangan Tarik Pada Balok Beton Bertulang Skala Model - Rexi Putra; Reni Suryanita; Ridwan Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Reinforced concrete (RC) beam is one of the structural elements that is often encountered in field applications and is a considerable element of its role in carrying flexural load. The purpose of this research is to analyze the pure bending behavior of RC beam in the form of stress on the reinforcement bars by using finite element method. Finite element analysis is done by using software LUSAS v.16. The load was applied at 2 points at a distance of 1/3 of beam span  from each supports and it was gradually increased until the beam  cracked. The result of yield tensile strength of reinforcement bar was 358.65 MPa. It was found that the tensile stress of the tension reinforcement bars in the event of  first crack was 72.1 MPa, while the tensile stress of these bars in the event of maximum applied load was 379.75 MPa. It can be concluded that the tensile reinforcement bars at the maximum load gained from the finite element analysis has yeilded. Keywords : Reinforced concrete beam, finite element, LUSAS v.16, tensile stress, first crack, maximum load.